2021
DOI: 10.3390/met11060961
|View full text |Cite
|
Sign up to set email alerts
|

Hardening by Transformation and Cold Working in a Hadfield Steel Cone Crusher Liner

Abstract: This paper presents the characterization of a secondary cone crusher concave liner made of Hadfield steel used in Chilean mining after crushing copper minerals during all service life. During use, a cone crusher concave liner suffers indentation (cold working) and abrasion; this combination provides the concave with a layer that constantly renews itself, maintaining a surface highly resistant to abrasive wear. The results presented here were obtained using optical microscopy, microhardness test, measuring abra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The used three-point bending analysis results showed that loading angle and position affect the deformation modes. In studies carried out on crushers that have a conical structure rather than a beam structure, heat treatment [18] was applied on a cone crusher surface to increase the resistance to abrasion. Gyratory crusher torque analysis [19] was analyzed with discrete element method and found that large particles cause to decrease the crushing torque.…”
Section: Methodsmentioning
confidence: 99%
“…The used three-point bending analysis results showed that loading angle and position affect the deformation modes. In studies carried out on crushers that have a conical structure rather than a beam structure, heat treatment [18] was applied on a cone crusher surface to increase the resistance to abrasion. Gyratory crusher torque analysis [19] was analyzed with discrete element method and found that large particles cause to decrease the crushing torque.…”
Section: Methodsmentioning
confidence: 99%
“…One approach is to increase the manganese alloy content up to 20% [11,12]. Another commonly used method is strain hardening [11][12][13][14][15]. However, strain hardening alone is not sufficient to significantly improve wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that the introduction of Si into the zinc bath promotes the rapid formation of Fe–Zn intermetallics in the coating. [ 10 ] Additionally, Bi incorporation has been shown to effectively minimize the thickness of the galvanized alloy layer and improve its mechanical characteristics. [ 11 ] Manganese enhances the layer's microstructure and can lead to a substantial 65% decrease in corrosion rate.…”
Section: Introductionmentioning
confidence: 99%